2016
DOI: 10.1007/s10695-016-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth, enzymatic glutathione peroxidase activity and biochemical status of juvenile barramundi (Lates calcarifer) fed dietary fermented soybean meal and organic selenium

Abstract: Solvent-extracted soybean meal (SBM) was fermented using baker's yeast Saccharomyces cerevisae at 30 °C for 5 days. Four isonitrogenous and isocaloric diets containing 75% SBM protein, either fermented or non-fermented (SBM and FSBM), and supplemented or not with organic Se (OS) (SBM and FSBM), were fed to triplicate groups of juvenile barramundi (Lates calcarifer) (initial weight of 5 g) for 75 days. A fishmeal (FM)-based diet formulated for juvenile barramundi was used as a reference diet. The growth of fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…Similarly, the inclusion of hydrolysates from krill, shrimp, and tilapia in the diets did not alter the qualitative descriptions of Hb in red sea bream ( Pagrus major ) ( Khosravi et al, 2015b ) . Furthermore, Ilham & Fotedar (2017) observed no significant variation in the Hb concentration in juvenile barramundi fed on fermented soybean meal supplemented with organic selenium. In the present study, the average hematocrit concentration ranged between 24% and 29.67%, which was below the normal range (30%–45%) suggested by Adams, Brown & Goede (1993) .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, the inclusion of hydrolysates from krill, shrimp, and tilapia in the diets did not alter the qualitative descriptions of Hb in red sea bream ( Pagrus major ) ( Khosravi et al, 2015b ) . Furthermore, Ilham & Fotedar (2017) observed no significant variation in the Hb concentration in juvenile barramundi fed on fermented soybean meal supplemented with organic selenium. In the present study, the average hematocrit concentration ranged between 24% and 29.67%, which was below the normal range (30%–45%) suggested by Adams, Brown & Goede (1993) .…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, a study by Azarm & Lee (2014) reported that fermented soybean meal prompted the enzymatic antioxidant GPx in blackhead sea bream ( Acanthopagrus schlegelii ), through the bioavailability of isoflavones produced by the microbial activity. Moreover, one of our previous studies suggested that an appropriate level of dietary inclusion of fermented lupin meal supports growth and the antioxidant GPx activity in juvenile barramundi ( Ilham & Fotedar, 2017 ). However, in the present study, the reduced GPx activity in the fish fed on TH 50 , FTH 50 , and FTH75 replacement diets compared to control may have been caused as a result of a higher inclusion level of TH rather than due to the fermentation process.…”
Section: Discussionmentioning
confidence: 95%
“…The imbalance between antioxidant defences and free radical generation may cause cell damage, which may provoke the leaking of liver enzymes particularly ALT and GLDH in fish [35], associated with liver cell damage. Although published data are available on the effects of plant protein on oxidative biomarkers of barramundi [21,22,36,37], there is less information on the effects of animal protein inclusions. The dietary inclusion of PBM impacted the liver health of barramundi by increasing the levels of ALT and GLDH [18], and animal protein ingredients elevated the levels of AST and ALT in hybrid grouper, Epinephelus fuscoguttatus♀× Epinephelus lanceolatus♂ [38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, blood biochemical evaluation has received considerable attention towards the development of aquafeed, especially for the clinical assessment of specific novel ingredients (Ilham & Fotedar, ; Norag et al, ; Wang et al, ). Previous findings when fish fed with various levels of ESBM (102.2–148 g/kg) to replace 150 g/kg dietary PBM supplemented with squid hydrolysates and squid meal did not show any clinical differences for total protein, albumin, glucose, cholesterol, bile acids, ALP, AST and ALT enzyme activities among the dietary treatments (Novriadi, Spangler et al, ).…”
Section: Discussionmentioning
confidence: 99%